The impact of household digital transformation on household energy efficiency: Empirical evidence from Chinese households. - Suxu Lin; Lin He; Xin Lin; Weicheng Li (PLoS ONE)
Carbon emissions from household consumption are an important part of global energy consumption, and household digital transformation is vital for realizing green and low-carbon development. Using data from the 2019 China Household Finance Survey, this study empirically examines the effect of household digital transformation on household energy efficiency. The results show that household digital transformation significantly improves household energy efficiency across all quantiles. This effect varies by consumption type, with the most pronounced improvements in food, housing, and other consumption categories. The impact is stronger for households with elderly members. Per capita household income and education level serve as important mediating and moderating mechanisms, respectively. Unlike previous macro-level studies, this research provides micro-evidence on the impact of household digital transformation on energy efficiency, explores the underlying mechanisms through income and education effects, and examines heterogeneous impacts across different consumption types and household characteristics. These findings offer important policy implications for leveraging digital transformation to enhance household energy efficiency and promote sustainable development.